Choosing The Right Software In Supporting The Successful of Enterprise ERP Implementation - Yodhie Yuniarthe; Idris Asmuni (Bandar Lampung University (UBL), 2013)
Enterprise Resource Planning is an integrated information system that involves many parties in the company's resources. Success factors in implementing ERP in addition to management is also supported by the implementation of adequate software. Critical success factors in the implementation is not perfect because it basically creates tension between resources are bridged with a ERP software integration appropriate to support the company's productivity. This paper outlines a summary of the procedures and how to implement ERP software to support the success of the previous research. Factors that led to the financial costs of ERP implementation risks are also considered in the selection of this software. Survey methodology used in this study as well as the implementation of measures that should be used as guidelines for software development-ready. The results showed that the full-time project managers choose the right, training personnel tend to bring a successful project implementation. This is impacting on the integration and application of software risks that will be applied to a particular time period. Given this research is expected the decision makers in the organization can improve enterprise information systems implementation in terms of implementation of software systems in accordance with company objectives.